2001
DOI: 10.1094/cchem.2001.78.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High and Low Molecular Weight Glutenin Subunits on Rheological Dough Properties and Breadmaking Quality of Wheat

Abstract: High molecular weight (HMW) or low molecular weight (LMW) subunits of different chemical state (reduced, reoxidized with KBrO3, or KIO3) or gliadins were added in 1% amounts to a base flour of the wheat cultivar Rektor and mixed with water. The corresponding doughs were then characterized by microscale extension tests and by microbaking tests and were compared to doughs from the base flour without additives. The maximum resistance of dough was strongly increased by HMW subunits in a reduced state and by HMW su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 8 publications
3
20
0
Order By: Relevance
“…According to Bekes et al 21 because glutenin subunits are part of the glutenin network, ‘addition’ of monomeric glutenin subunits to a flour provides a less realistic indication of their functional role than chemical ‘incorporation’ into the glutenin network. They developed ‘incorporation’ protocols to study these subunits in doughs and this approach has been adopted by others 15, 17, 18, 35, 40. However, others have found that there is a similarity between the effects of ‘addition’ and ‘incorporation’ of glutenin subunits on dough properties 14, 41.…”
Section: Resultsmentioning
confidence: 99%
“…According to Bekes et al 21 because glutenin subunits are part of the glutenin network, ‘addition’ of monomeric glutenin subunits to a flour provides a less realistic indication of their functional role than chemical ‘incorporation’ into the glutenin network. They developed ‘incorporation’ protocols to study these subunits in doughs and this approach has been adopted by others 15, 17, 18, 35, 40. However, others have found that there is a similarity between the effects of ‘addition’ and ‘incorporation’ of glutenin subunits on dough properties 14, 41.…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for the reduced rate and strength of gluten agglomeration in flour-water doughs and slurries have not been fully understood. High molecular weight glutenins and glutenin macropolymer formed by the glutenin particles have been shown in the last 10 years to add strength (elasticity) to a wheat flour dough (Antes & Wieser, 2001;Bekkers, Lichtendonk, Graveland, & Plijter, 2000;Don, Lichtendonk, Plijter, & Hamer, 2003aSchropp & Weiser, 1996;Singh & MacRitchie, 2001;Southan & MacRitchie, 1999;Uthayakumaran, Stoddard, Gras, & Bekes, 2000;Veraverbeke, Verbruggen, & Delcour, 1998;Wooding, Kavale, MacRitchie, & Stoddard, 1999). However, the wet-processing quality of a wheat flour and its relationship to flour protein quality remain mostly unknown.…”
Section: Wet-milling Properties Of Flours By Dough-washing (Dw) Methodsmentioning
confidence: 99%
“…The reasons for the various rates of the gluten aggregation in flour-water doughs and slurries are not fully understood. High-molecular weight gluten subunits (HMW-GS) and glutenin macropolymer (GMP) gel formed by the glutenin particles have been shown in the last 10 years to add strength (elasticity) to a wheat flour dough (Schropp & Wieser, 1996;Veraverbeke, Verbruggen, & Delcour, 1998;Southan & MacRitchie, 1999;Wooding, Kavale, MacRitchie, & Stoddard, 1999;Bekkers, Lichtendonk, Graveland, & Plijter, 2000;Uthayakumaran, Stoddard, Gras, & Bekes, 2000;Antes & Wieser, 2001;Singh & MacRitchie, 2001;Don, Lichtendonk, Plijter, & Hamer, 2003a, b). The aggregation rate of gluten proteins in a Batter process appears to be accelerated by the increasing level of glutenin proteins (Roels et al, 1998a, b).…”
Section: Significance Of Wheat Flour Components In Wet-millingmentioning
confidence: 99%